The democratic experience in the labyrinth of political cultures - Carrizo, Bernardo (Universidad Nacional del Litoral, 2021)
This article presents the main guidelines of a research project that addresses the network of political cultures that constitute democracy in its many faces. The research proposes an articulation between the national, subnational and regional aspects of Argentine democracy as a historical experience, during the 20th century and the beginning of the 21st century. These temporal-spatial coordinates are supported by the hypothesis according to which different spaces of politics production can be recognized in such a way that their study contributes to illuminate and clarify aspects of the historical process that are difficult to recover in a vision strictly centered on the national perspective. The project builds its object by seeking to recover the articulation between practices, discourses and ideas as components of political cultures that can be recognized in the period. The project aims to consolidate an enriching dialogue between disciplines, since political phenomena are dynamic and the limits of the political are flexible, so it will appeal to a complex and interdisciplinary methodological construction of observation in order to adapt to the high levels of uncertainty, contingency and risk that the object summons.